Best infection control practices for intradermal, subcutaneous, and intramuscular needle injections - Hutin Yvan; Hauri Anja; Chiarello Linda; Catlin Mary; Stilwell Barbara; Ghebrehiwet Tesfamicael; Garner Julia (Bulletin of the World Health Organization, 2003)
OBJECTIVE: To draw up evidence-based guidelines to make injections safer. METHODS: A development group summarized evidence-based best practices for preventing injection-associated infections in resource-limited settings. The development process included a breakdown of the WHO reference definition of a safe injection into a list of potentially critical steps, a review of the literature for each of these steps, the formulation of best practices, and the submission of the draft document to peer review. FINDINGS: Eliminating unnecessary injections is the highest priority in preventing injection-associated infections. However, when intradermal, subcutaneous, or intramuscular injections are medically indicated, best infection control practices include the use of sterile injection equipment, the prevention of contamination of injection equipment and medication, the prevention of needle-stick injuries to the provider, and the prevention of access to used needles. CONCLUSION: The availability of best infection control practices for intradermal, subcutaneous, and intramuscular injections will provide a reference for global efforts to achieve the goal of safe and appropriate use of injections. WHO will revise the best practices five years after initial development, i.e. in 2005.